Correction: Magnitude and determinants of improved household latrine utilization in Ethiopia: Multilevel analysis of the mini Ethiopian Demographic Health Survey (EDHS) 2019. - Aragaw Tesfaw; Mulu Tiruneh; Melkalem Mamuye; Zebader Walle; Wondwosen Teshager; Fentaw Teshome; Alebachew Taye; Wondimnew Dessalegn; Gashaw Walle; Asaye Alamneh Gebeyehu (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0289427.].